The Role of HLA-G Molecule and HLA-G Gene Polymorphisms in Tumors, Viral Hepatitis, and Parasitic Diseases - Dias, Fabrício C.; Castelli, Erick C.; Collares, Cristhianna V. A.; Moreau, Philippe; Donadi, Eduardo A. (Frontiers in Immunology, 2015)
Considering that the non-classical HLA-G molecule has well-recognized tolerogenic properties, HLA-G expression is expected to be deleterious when present in tumor cells and in cells chronically infected by viruses, whereas HLA-G expression is expected to be advantageous in autoimmune disorders. The expression of HLA-G on tissue or peripheral blood cells, the levels of soluble HLA-G and polymorphic sites along the gene have been studied in several disorders. In this study, we revised the role of the molecule and polymorphic sites along the HLA-G gene in tumors, viral hepatitis and parasitic disorders. Overall, several lines of evidence clearly show that the induction of HLA-G expression in tumors has been associated with worse disease outcome and disease spread. In addition, the few studies conducted on hepatitis and parasitic disorders indicate that HLA-G may contribute to disease pathogenesis. Few isolated polymorphic sites, primarily located at the coding or 3’ untranslated HLA-G region, have been evaluated in these disorders, and a complete HLA-G typing together with the study of gene regulatory elements may further help on the understanding of the influence of the genetic background on disease susceptibility.